Effects of Prehospital Thrombolysis in Stroke Patients With Prestroke Dependency. Issue 3 (March 2018) - Nolte, Christian H.; Ebinger, Martin; Scheitz, Jan F.; Kunz, Alexander; Erdur, Hebun; Geisler, Frederik; Braemswig, Tim Bastian; Rozanski, Michal; Weber, Joachim E.; Wendt, Matthias; Zieschang, Katja; Fiebach, Jochen B.; et al.
Abstract : Background and Purpose—: Data on effects of intravenous thrombolysis on outcome of patients with ischemic stroke who are dependent on assistance in activities of daily living prestroke are scarce. Recent registry based analyses in activities of daily –independent patients suggest that earlier start of intravenous thrombolysis in the prehospital setting leads to better outcomes when compared with the treatment start in hospital. We evaluated whether these observations can be corroborated in patients with prestroke dependency. Methods—: This observational, retrospective analysis included all patients with acute ischemic stroke depending on assistance before stroke who received intravenous thrombolysis either on the Stroke Emergency Mobile (STEMO) or through conventional in-hospital care (CC) in a tertiary stroke center (Charité, Campus Benjamin Franklin, Berlin) during routine care. Prespecified outcomes were modified Rankin Scale scores of 0 to 3 and survival at 3 months, as well as symptomatic intracranial hemorrhage. Outcomes were adjusted in multivariable logistic regression. Results—: Between February 2011 and March 2015, 122 of 427 patients (28%) treated on STEMO and 142 of 505 patients (28%) treated via CC needed assistance before stroke. Median onset-to-treatment times were 97 (interquartile range, 69–159; STEMO) and 135 (interquartile range, 98–184; CC; P <0.001) minutes. After 3 months, modified Rankin Scale scores of 0 to 3 was observed in 48 STEMO patients (39%) versus 35 CC patients (25%; P =0.01) and 86 (70%, STEMO) versus 85 (60%, CC) patients were alive ( P =0.07). After adjustment, STEMO care was favorable with respect to modified Rankin Scale scores of 0 to 3 (odds ratio, 1.99; 95% confidence interval, 1.02–3.87; P =0.042) with a nonsignificant result for survival (odds ratio, 1.73; 95% confidence interval, 0.95–3.16; P =0.07). Symptomatic intracranial hemorrhage occurred in 5 STEMO versus 12 CC patients (4.2% versus 8.5%; P =0.167). Conclusions—: The results of this study suggest that earlier, prehospital (as compared with in-hospital) start of intravenous thrombolysis in acute ischemic stroke may translate into better clinical outcome in patients with prestroke dependency. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT02358772.